Modulation of Repeated Anodal HD-tDCS on Attention in Healthy Young Adults - Lu, Hongliang; Liu, Quanhui; Guo, Zhihua; Zhou, Guangxin; Zhang, Yajuan; Zhu, Xia; Wu, Shengjun (Frontiers in Psychology, 2020)
High-definition transcranial direct current stimulation (HD-tDCS) is a valid brain stimulation technology to optimize cognitive function. Recent evidences indicate that short-term or single anodal tDCS session will enhance attention function, however, the variation of attention modulated by repeated anodal HD-tDCS over a longer period of time is unexplored. We examined the modulation pattern of repeated HD-tDCS sustained for four weeks on attention function in healthy young participants (39 young adults). The results showed a robust benefit of anodal HD-tDCS on executive control and selective attention, but not orienting or alerting, increased successively over 4 weeks, and the enhancement on executive control of each week was significant compared to baseline in anodal group. In addition, the test performance about executive control and selective attention gradually restored to initial level in sham group, which appeared obviously from week 3 (after 9 interventions), but the improvement of attention in anodal group was persistent. We conclude that repeated anodal high definition HD-tDCS provides positive benefit on executive control and selective attention, and has obvious accumulative effect after 9 or more times intervention compared to sham HD-tDCS. Additionally, our findings might provid a pivotal guidence for the formulation of the strategy for long-term anodal HD-tDCS modulation on attention function.